2004
DOI: 10.1007/s10151-004-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

Five-year survival after curative resection for adenocarcinoma of the colon

Abstract: The treatment of colon adenocarcinoma with curative resection by the end of the 20th century is accompanied with acceptable rates of overall 5-year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
6
0
5
Order By: Relevance
“…; that of patients without hepatic metastasis is 69.5% to 95.7% (5,6). Thus, early detection of liver metastasis is important for improving patient survival.…”
mentioning
confidence: 99%
“…; that of patients without hepatic metastasis is 69.5% to 95.7% (5,6). Thus, early detection of liver metastasis is important for improving patient survival.…”
mentioning
confidence: 99%
“…A variety of colonic anastomotic techniques have been described in the literature. Recent randomized studies have demonstrated that in patients with colonic anastomoses, stapling procedures, omentoplasty and abdominal drainage do not reduce the rate of anastomotic leakage [2,3,5]. Manually constructed anastomoses in colonic surgery are as safe as stapled ones.…”
Section: Risk Factors For Anastomotic Dehiscencementioning
confidence: 99%
“…General risk factors such as malnutrition, weight loss, diabetes, steroids, multiple blood transfusions, smoking and excessive alcohol use have not been significantly predictive of anastomotic failure [2,4].…”
Section: Risk Factors For Anastomotic Dehiscencementioning
confidence: 99%
See 2 more Smart Citations